2018
DOI: 10.1021/acs.nanolett.8b01640
|View full text |Cite
|
Sign up to set email alerts
|

Disordered Nanoparticle Packings under Local Stress Exhibit Avalanche-Like, Environmentally Dependent Plastic Deformation

Abstract: Nanoindentation experiments on disordered nanoparticle packings performed both in an atomic force microscope and in situ in a transmission electron microscope are used to investigate the mechanics of plastic deformation. Under an applied load, these highly porous films exhibit load drops, the magnitudes of which are consistent with an exponential population distribution. These load drops are attributed to local rearrangements of a small number of particles, which bear similarities to shear transformation zones… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…Another notable feature is a large enclosed area between the loading and unloading segments of the force–displacement curve obtained from LD compression, which typifies large energy absorption. The net energy dissipated ( E diss ) during the test is the cyclic integral of the load–displacement curve, [ 30 ] which is the difference in the total work done during mechanical loading and the recovered elastic work during unloading [ 31 ] Ediss=Fdh…”
Section: Resultsmentioning
confidence: 99%
“…Another notable feature is a large enclosed area between the loading and unloading segments of the force–displacement curve obtained from LD compression, which typifies large energy absorption. The net energy dissipated ( E diss ) during the test is the cyclic integral of the load–displacement curve, [ 30 ] which is the difference in the total work done during mechanical loading and the recovered elastic work during unloading [ 31 ] Ediss=Fdh…”
Section: Resultsmentioning
confidence: 99%
“…This includes substantial particle-level spatial heterogeneity in stiffness, energy dissipation, and the amount of plasticity. This agreement is attained when using a value of adhesion several times greater than the van der Waals adhesion value for the nanoparticles, suggesting that stronger bonding mechanisms such as covalent bonds, hydrogen bonds, or capillary forces were present in the experiments. We have also shown that thermal activation can be omitted in our DNPs wherein strong dissipation exists, despite the fact that the constituent particles are nanoscale in size.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, we altered interparticle interactions by introducing water vapor into the system, leading to the formation of liquid bridges between nanoparticles via capillary condensation. 12 Nevertheless, it is difficult to quantitatively determine how capillary bridges affect adhesion forces at this nanometer length scale. Therefore, this method is not a perfect analog for tuning adhesion.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations